2019
DOI: 10.1007/s13596-019-00395-9
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of anti-nociceptive and anti-inflammatory activities of Piper sylvaticum (Roxb.) stem by experimental and computational approaches

Abstract: Piper sylvaticum Roxb., (Family: Piperaceae), commonly known as pahaari peepal, is used in traditional medicine for the treatment of rheumatic pain, headache, asthma, chronic cough, diarrhea, and wounds. To provide scientiic proof for its traditional use, the present study was designed to investigate the antinociceptive and anti-inlammatory properties of methanol extract of P. sylvaticum stem (MEPSS) in pain models. Additionally, computational studies viz. molecular docking, ADME and toxicological property pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 35 publications
1
20
0
Order By: Relevance
“…It was observed that two compounds 7 and 17c were found as significant hMAO-A inhibitors with IC 50 values 15.38 ± 0.071 µM and 16.11 ± 0.091 µM, respectively. The docking scores of the compounds 7 and 17c as − 9.72 and − 7.98 was also in agreement with the in vitro results [16,17]. However, the reference compound clorgyline and piperine showed hMAO-A inhibitory activity with IC 50 values of 18.74 ± 0.096 µM and 19.01 ± 0.031 µM, respectively.…”
Section: Discussionsupporting
confidence: 85%
“…It was observed that two compounds 7 and 17c were found as significant hMAO-A inhibitors with IC 50 values 15.38 ± 0.071 µM and 16.11 ± 0.091 µM, respectively. The docking scores of the compounds 7 and 17c as − 9.72 and − 7.98 was also in agreement with the in vitro results [16,17]. However, the reference compound clorgyline and piperine showed hMAO-A inhibitory activity with IC 50 values of 18.74 ± 0.096 µM and 19.01 ± 0.031 µM, respectively.…”
Section: Discussionsupporting
confidence: 85%
“…Three-dimensional crystallographic structures of enzyme/receptors were obtained from the Protein Data Bank RCSB PDB [36]: potassium channel receptor (PDB: 4UUJ) [37], human serotonin receptor (PDB: 5I6X) [38], cyclooxygenase-1 (COX-1, PDB: 2OYE) [39], cyclooxygenase-2 (COX-2, PDB: 3HS5) [40], and xanthine oxidoreductase enzyme (PDB: 1R4U) [41]. The enzyme/receptor was prepared for a docking experiment using Protein Preparation Wizard [42], which embedded in Schrödinger suite-Maestro v 10.1, as we described previously [43].…”
Section: Molecular Docking Analysis: Enzyme/receptor Preparationmentioning
confidence: 99%
“…Finally, the resultant mixture was filtered through a cotton plug, followed by Whatman No.1 filter paper (Sigma-Aldrich, St. Louis, MO, USA), and the filtrate solution evaporated to yield the methanol extract of P. sylvaticum leaves and stems (MEPSL and MEPSS). The detailed procedure was described in our previous articles-see materials and methods sections [9,11].…”
Section: Preparation Of Extractmentioning
confidence: 99%
“…The preliminary qualitative phytochemical analysis of this plant (leaves and stem) revealed the presence of several phytochemicals, including alkaloids, flavonoids, carbohydrates, tannins, and saponins. Additionally, an earlier quantitative phytochemical study of this plant reported that the plant contains substantial amounts of phenols (65.83 and 93.39 mg GAE/g dried extract), flavonoids (102.56 and 53.74 mg QE/g dried extract), and condensed tannins (89.32 and 55.82 mg CE/g dried extract) in the leaves and stem [9,11]. Besides, several phytoconstituents have been isolated from this plant, such as piperine, piperlonguminine, sylvamide, sylvatesmin, sylvatine, sylvone, piperic acid, sesamin, and beta-sitosterol; most of them are fall into the categories of alkaloids, alkamides, flavone, and lignins [9,12].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation